2013
DOI: 10.2527/jas.2012-5949
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-by-environment interaction of growth traits in rainbow trout (Oncorhynchus mykiss): A continental scale study1

Abstract: Rainbow trout is a globally important fish species for aquaculture. However, fish for most farms worldwide are produced by only a few breeding companies. Selection based solely on fish performance recorded at a nucleus may lead to lower-than-expected genetic gains in other production environments when genotype-by-environment (G × E) interaction exists. The aim was to quantify the magnitude of G × E interaction of growth traits (tagging weight; BWT, harvest weight; BWH, and growth rate; TGC) measured across 4 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…Furthermore, it is optimum to record the sib's performance in the production environment (IFSLT environment or other environment similar to the IFS environment) to increase the accuracy of selection and for future genetic evaluations of later generations. The genetic correlation across environments for K (0.78) was near the break-even correlation (≥ 0.70) in aquaculture, as suggested by Sae-Lim et al (2013). The break-even genetic correlation is the intersection of genetic correlations where the genetic gains from different breeding strategies are identical and can be used as a criterion to select a proper breeding strategy (Mulder et al, 2006).…”
Section: Implications For Breedingmentioning
confidence: 85%
See 3 more Smart Citations
“…Furthermore, it is optimum to record the sib's performance in the production environment (IFSLT environment or other environment similar to the IFS environment) to increase the accuracy of selection and for future genetic evaluations of later generations. The genetic correlation across environments for K (0.78) was near the break-even correlation (≥ 0.70) in aquaculture, as suggested by Sae-Lim et al (2013). The break-even genetic correlation is the intersection of genetic correlations where the genetic gains from different breeding strategies are identical and can be used as a criterion to select a proper breeding strategy (Mulder et al, 2006).…”
Section: Implications For Breedingmentioning
confidence: 85%
“…A sea bass experiment was performed under two water temperatures by Saillant et al (2006), and a significant G × E interaction was reported. Similar G × E interactions between different environments have been discovered in other aquaculture species (Evans and Langdon, 2006;Kvingedal et al, 2010;Sae-Lim et al, 2013;Trọng et al, 2013). Thus, a G × E interaction may occur in turbot when they are reared in different environments under different water temperatures.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Significant GxE interactions for growth in aquaculture have occurred due to differences in temperature, salinity, stocking density and between recirculation, pond and cage facilities (Sylven et al, 1991;Myers et al, 2001;Ponzoni et al, 2005;Saillant et al, 2006;Eknath 2007;Khaw et al, 2009;Mas-Muñoz et al, 2013) with estimates for body weight at harvest in different environments as low as 0.19+0.13 (Sae-Lim et al, 2013). There is also an emerging need for GxE assessment of growth rate in newly formulated diets with significant re-ranking of family performances between diets observed by Pierce et al (2008), Dupont-Nivet et al…”
Section: Accepted M Manuscriptmentioning
confidence: 99%